Biocontrol Strains Differentially Shift the Genetic Structure of Indigenous Soil Populations of Aspergillus flavus - Lewis, Mary H.; Carbone, Ignazio; Luis, Jane M.; Payne, Gary A.; Bowen, Kira L.; Hagan, Austin K.; Kemerait, Robert; Heiniger, Ron; Ojiambo, Peter S. (Frontiers in Microbiology, 2019)
Biocontrol using non-aflatoxigenic strains of Aspergillus flavus has the greatest potential to mitigate aflatoxin contamination. However, factors that influence the efficacy of biocontrol agents under field conditions are not well understood. Shifts in the genetic structure of indigenous soil populations of A. flavus following application of biocontrol products Afla-Guard and AF36 were investigated to determine how these changes influence the efficacy of biocontrol strains. Soil samples were collected from maize fields in Alabama, Georgia and North Carolina in 2012 and 2013 to determine the population genetic structure of A. flavus following application of the biocontrol strains. A. flavus L was the most dominant species of Aspergillus section Flavi followed by A. parasiticus. A total of 112 multilocus haplotypes (MLHs) were inferred from 1,282 isolates of A. flavus L using multilocus sequence typing of the trpC, mfs and AF17 loci. A. flavus individuals belonging to the Afla-Guard MLH in the IB lineage were the most dominant, while individuals of the AF36 MLH in the IC lineage were recovered in very low frequencies. There were no significant (P > 0.05) differences in the frequency of individuals with MAT1-1 and MAT1-2, an indication of a recombining population resulting from sexual reproduction. Population mean mutation rates were not different across temporal and spatial samples indicating that mutation alone is not a driving force in observed multilocus sequence diversity. Clustering based on principal component analysis identified two distinct evolutionary lineages (IB and IC) across all three states. Additionally, patristic distance analysis revealed phylogenetic incongruency among single locus phylogenies which suggests ongoing genetic exchange and recombination. Levels of aflatoxin accumulation were very low except in North Carolina in 2012, where aflatoxin levels were significantly (P < 0.05) lower in grain from treated compared to untreated plots. Phylogenetic analysis showed that Afla-Guard was more effective than AF36 in shifting the indigenous soil populations of A. flavus towards the non-toxigenic or low aflatoxin producing IB lineage. These results suggest that Afla-Guard is likely to be more effective in reducing aflatoxin accumulation and will also persist longer in the soil than AF36 in the southeastern United States.